2020
DOI: 10.31234/osf.io/ebw6p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age Inclusive Human Resource Practices, Age Diversity Climate, and Work Ability: Exploring Between- and Within-Person Indirect Effects

Abstract: To address the challenges imposed by demographic change, organizations have becomeincreasingly interested in maintaining and improving employees’ work ability across the working lifespan. Based on signaling and social exchange theories, we present a study that investigates the indirect influence of age inclusive human resource practices on work ability through age diversity climate. Using a six-wave longitudinal study of n = 355 employees, we model between- and within-person mediated effects using a random int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…This length of time lag is in line with the recommendations of Dormann and Griffin (2015) of a relatively short time lags in survey research focusing on psychosocial work characteristics and worker outcomes. Moreover, a time lag of 6 months was considered appropriate as previous studies have demonstrated that the outcomes included in this study can fluctuate in rather short periods (De Lange et al, 2004;Zacher et al, 2014;Akkermans et al, 2019;Rudolph and McGonagle, 2019;Rudolph and Zacher, 2020). The first questionnaire (T1) was sent to the participants between November 2017 and the end of January 2018, the second questionnaire (T2) between June 2018 and the middle of August 2018.…”
Section: Design Of the Study And Proceduresmentioning
confidence: 99%
“…This length of time lag is in line with the recommendations of Dormann and Griffin (2015) of a relatively short time lags in survey research focusing on psychosocial work characteristics and worker outcomes. Moreover, a time lag of 6 months was considered appropriate as previous studies have demonstrated that the outcomes included in this study can fluctuate in rather short periods (De Lange et al, 2004;Zacher et al, 2014;Akkermans et al, 2019;Rudolph and McGonagle, 2019;Rudolph and Zacher, 2020). The first questionnaire (T1) was sent to the participants between November 2017 and the end of January 2018, the second questionnaire (T2) between June 2018 and the middle of August 2018.…”
Section: Design Of the Study And Proceduresmentioning
confidence: 99%